The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.30574/gscbps.2022.20.1.0285
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the factors affecting covid-19 vaccine acceptance among the university students of Centro Escolar University-Manila

Abstract: The disease outbreak, Coronavirus 2019 (COVID-19), occurred in December 2019 in Wuhan, China and later spread throughout the world. As a result, community quarantines were implemented and school systems have undergone transition as mandated by the government. While the facts about the vaccines have expanded significantly across different demographics, there’s still a significant amount of hesitancy among younger groups, and even more so due to conflicting views of the importance of vaccines and vaccination equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Bellon (2021) revealed the existence of COVID-19 hesitancy among healthcare workers anchored on the fear of potential side effects and philosophical or religious beliefs that prohibit vaccination aside from medical contraindications to receiving the COVID-19 vaccine. Capis et al (2022) found no significant difference in COVID-19 vaccine acceptance between medical and non-medical students. The authors attributed the acceptance by medical students to their knowledge of clinical trials about the process involved in medicine production.…”
Section: Academic Discipline and Covid-19 Vaccine Hesitancymentioning
confidence: 60%
“…Bellon (2021) revealed the existence of COVID-19 hesitancy among healthcare workers anchored on the fear of potential side effects and philosophical or religious beliefs that prohibit vaccination aside from medical contraindications to receiving the COVID-19 vaccine. Capis et al (2022) found no significant difference in COVID-19 vaccine acceptance between medical and non-medical students. The authors attributed the acceptance by medical students to their knowledge of clinical trials about the process involved in medicine production.…”
Section: Academic Discipline and Covid-19 Vaccine Hesitancymentioning
confidence: 60%